A mode-locked random laser generating transform-limited optical pulses - Jean Pierre von der Weid; Marlon M. Correia; Pedro Tovar; Anderson S. L. Gomes; Walter Margulis (Nature Communications, 2024)
Abstract Ever since the mid-1960’s, locking the phases of modes enabled the generation of laser pulses of duration limited only by the uncertainty principle, opening the field of ultrafast science. In contrast to conventional lasers, mode spacing in random lasers is ill-defined because optical feedback comes from scattering centres at random positions, making it hard to use mode locking in transform limited pulse generation. Here the generation of sub-nanosecond transform-limited pulses from a mode-locked random fibre laser is reported. Rayleigh backscattering from decimetre-long sections of telecom fibre serves as laser feedback, providing narrow spectral selectivity to the Fourier limit. The laser is adjustable in pulse duration (0.34–20 ns), repetition rate (0.714–1.22 MHz) and can be temperature tuned. The high spectral-efficiency pulses are applied in distributed temperature sensing with 9.0 cm and 3.3 × 10−3 K resolution, exemplifying how the results can drive advances in the fields of spectroscopy, telecommunications, and sensing.